THE FORTIFICATION OF PROTEIN HYDROLYSATE OF REBON SHRIMP (Mysis relicta) TO THE QUALITY OF PEMPEK PREMIX FLOUR - Maya Fitri Zuly; Suparmi Suparmi; Dewita Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The purpose of the research was to observe theeffect of fortificationprotein hydrolysateof rebon shrimp on the quality of pempek premix flour. The research was conducted at the Laboratory of Fishery Technology, the Laboratory ofFisheryChemical, the Integrated Laboratory in the Fisheries and MarineFaculty, and the Laboratory ofNatural Ingredients and Minerals inFaculty of Engineering Riau University Pekanbaru in February-March2019. The research used an experimental method with four different treatments, namely: no premix flour added or 0% (control), 5%, 10%, and 15% of rebon shrimp hydrolyzate protein and repeated for tree times. The variables assessedwereorganoleptic quality organoleptik (appearance, odor, and texture) and the proximate composition, including thecontent of water,protein, lipid, and ash. The results showed that the fortification of hydrolysate protein rebon shrimpat the concentration of 10% was the best treatment and in accordance to the standards of the quality of the seasoning flour (SNI 01-4476-1998).The value of the organoleptic quality were being showed by the score of appearance at 7,03 with criteria clean, normal, bright; odor at 7,43 with the criteria very delicious scents, wafted the smell of rebon shrimp and seasoning; and value of texture at 7,27 with the criteria not lumpy, quite dry and smooth.The content of moisture was 3,02%, protein was 12,39%, lipid was 0,27%, and ash was 2,88%. Based on organoleptic evaluation,thepempekproducts made from the best treatment of premix flour showed that the acceptance of appearance was 100%, aroma was 90%, texture was 100%, and the taste was 100%. Keywords: Hydrolysate protein, rebon shrimp, premix flour, pempek (urutkan abjat)